At the edge of the orchard [large type] : a novel - Chevalier, Tracy (Wheeler Publishing large print hardcover, 2016)
James Goodenough, whose family had originally settled in Connecticut from England brings his family to Ohio to carve out a new life for them in the Black Swamp in 1838. As swamp fever gradually picks off their children and they wrestle daily with survival. This course will see their family engulfed in tragedy and fifteen years later we pick up with their youngest son, Robert who has been running west since the trying to escape his memories of what happened, taking solace in a very different kind of tree--the redwoods and sequoias of California. But Robert's past catches up with him and he's forced to confront what he's running from and work out for himself that you can't run for ever.